2000
DOI: 10.1002/1098-2396(20001215)38:4<477::aid-syn13>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity and occupancy of brain cannabinoid CB1 receptors by the antagonist/inverse agonist AM281

Abstract: The goals of this study were to examine the relationship between intravenous doses of the cannabinoid CB1 receptor antagonist AM281 (N‐(morpholin‐4‐yl)‐5‐(4‐iodophenyl)‐1‐(2,4‐dichlorophenyl)‐4‐methyl‐1H‐pyrazole‐3‐carboxamide) and the degree of occupancy of this receptor, and to relate occupancy to the ability of this compound to antagonize the sedative effects of the cannabinoid receptor agonist WIN 55,212‐2. Occupancy was determined by measuring the ability of intravenous doses of AM281 to inhibit in vivo b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 26 publications
6
24
0
Order By: Relevance
“…While occupancy measurements have previously been reported using [ 131 I]AM281 (Cosenza et al 2000), we have described here a more advantageous in vivo central CB 1 receptor occupancy method, this one using commercially available [ 3 H]SR141716A. Employing this method, we demonstrated that SR141716A and SLV319 occupy cortical CB 1 receptors consistently between 1 and 3 h after dosing.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…While occupancy measurements have previously been reported using [ 131 I]AM281 (Cosenza et al 2000), we have described here a more advantageous in vivo central CB 1 receptor occupancy method, this one using commercially available [ 3 H]SR141716A. Employing this method, we demonstrated that SR141716A and SLV319 occupy cortical CB 1 receptors consistently between 1 and 3 h after dosing.…”
Section: Discussionmentioning
confidence: 82%
“…The occupancy method described here offers certain methodological advances compared to the study by Cosenza et al (2000). Specifically, in the latter study, the nonspecific binding was estimated using an area thought to contain very low or no CB 1 receptor density, the brain stem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two deficiencies apply to most radiotracers developed to date for the CB 1 receptor. These ligands have been based on the structures of rimonabant (Cosenza et al, 2000;Gatley et al, 1996;Horti et al, 2006;Katoch-Rouse et al, 2003;Mathews et al, 2000Mathews et al, , 2002, cannabinoids (Charalambous et al, 1991), and alkylindoles (Gifford et al, 2002;Tamagan et al, 1999). In contrast to these older agents, 11 C-JHU75528 is a notable exception (see 'Discussion') and has moderate brain uptake and specific signal (Horti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Two less potent CB 1 -selective analogs, AM251 and AM281 ( Fig. 1), have also been reported (Gatley et al, 1997(Gatley et al, , 1998Lan et al, 1999;Cosenza et al, 2000). It is believed that the antagonistic activity of the diarylpyrazoles is attributable to the structural properties of 1-and 5-substituents, whereas the 3-substituent appears to be involved in agonism and receptor activation (Wiley et al, 2001).…”
mentioning
confidence: 97%